Analysis The Use of Schoology E-Learning Towards Students’ Learning Motivation Enhancement in STKIP Surya - Mira Rosalina (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The purpose of this research is to analyze the use of schoology e-learning as one of the supporting media towards students’ learning motivation enhancement and students’ opinion about the use of schoology e-learning. This research uses the qualitative descriptive as methods. Sampling was done with non-random sampling of 30 students from the STKIP Surya. Data were collected using a questionnaire, observation sheet, interview, and documentation which were analyzed descriptively. Data collected as much as twice to get more accurate result. The first data set is used to provide with a temporary conclusion, verification data conducted in the second data collecting. If data obtained on both have conformity, it can be made into final conclusion. The study uses blended learning model that integrates between traditional face to face instruction and e-learning. The result of the study found that: 1) Percentage of Likert Scale overall from the first and second data collection result got the same category i.e 77.30% and 79.05% with very high category which means the students were motivated using schoology e-learning, 2) The result of observation sheet in the first and the second data collecting got the same result that most student were happy to learn using schoology e-learning,3) The result of interview between the two were the same that means most students were motivated by learning using schoology e-learning because of its easyness, friendly look, and challenging way of doing the task. Keywords: schoology e-learning, descriptive qualitative method, blended learning, students’ learning motivation